JoJo's bizarre adventure. Part 6, Stone ocean. Volume 9 - Araki, Hirohiko, 1960- (Shonen Jump manga., 2025)
"After having narrowly escaped from Weather Forecast, Pucchi finally reaches the Time for Heaven and unlocks the Stand Maiden Heaven. Both the Stand and Pucchi himself fight with what is close to godlike, universe-destroying power. Can Jolyne and her friends manage to stop the evil priest once and for all? Don't miss the thrilling conclusion of JoJo's Bizarre Adventure Part 6: Stone Ocean."--viz.com.